2003
DOI: 10.1023/a:1026224901243
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study investigated the effects of consumer-provider racial match on consumer service satisfaction and treatment outcomes (i.e., Client Satisfaction Questionnaire and GAF-Posttest) of 96 outpatient consumers, 66 of whom were adults and 30 of whom were parent/caregivers of child consumers. Data was obtained by telephone interviews over a 6-week period. After controlling for four other variables, client satisfaction was higher for racially matched consumers. Racially matched child consumers also had higher G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…Given the large number of White American admissions (i.e., 10,211 treatment episodes), we used a random number generator to select a sample of 200 White American patients to serve as the comparison group. An a priori power analysis based on prior research (e.g., Gamst et al, 2003) indicated that 200 would be sufficient to detect differences in the outcome variables of interest (e.g., scores of levels of functioning). All of the Asian American admissions and the randomly selected White American admissions were manually searched in the hospital electronic medical records system to ensure that the treatment episode met study eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Given the large number of White American admissions (i.e., 10,211 treatment episodes), we used a random number generator to select a sample of 200 White American patients to serve as the comparison group. An a priori power analysis based on prior research (e.g., Gamst et al, 2003) indicated that 200 would be sufficient to detect differences in the outcome variables of interest (e.g., scores of levels of functioning). All of the Asian American admissions and the randomly selected White American admissions were manually searched in the hospital electronic medical records system to ensure that the treatment episode met study eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…While the MAIP has historically been used to examine the effects of fundamental constructs such as client-practitioner ethnic/racial match (e.g., Gamst, Dana, Der-Karabetian, & Kramer, (2000); Gamst et al, 2003), acculturation and ethnic identity (Gamst et al, 2002), and practitioner self-reported cultural competence (Gamst et al, 2004; Keyser, Gamst, Meyers, Der-Karabetian, & Morrow, 2014) on clinical outcomes, the client multicultural status assessment phase of the MAIP model can also be expanded to other contexts and phenomena in which cultural variables impact actions and thoughts. One such expansion is the phenomenon of shifting, particularly with respect to African American women.…”
mentioning
confidence: 99%
“…Twenty-one studies discussed the dimension of acceptability in relation to how Asian immigrant youth access MHSU services [ 109 128 ]. Several studies found that Asian cultural values can give rise to public stigma, stigma by close others (e.g., family or friends), and self-stigma, which decrease acceptability of MHSU service use [ 109 , 118 122 , 125 , 127 , 129 ].…”
Section: Resultsmentioning
confidence: 99%